The Effect of Education of Women of Childbearing Age and Household Income on Fertility with Age at First Marriage as an Intervening Variable - Wiranto, Edy; Pulubuhu, Dwia Aries Tina; T., M. Ramli A. (International Journal of Science and Society, 2023)
This research examines the influence of education of women of childbearing age, household income and age at first marriage as intervening variables on fertility in South Kalimantan Province. This research uses data from the 2022 National Socio-Economic Survey. The unit of analysis for this research is ever-married women aged 15 to 49 years. The analysis technique used is path analysis. The research results show that education of women of childbearing age and household income have a significant effect on fertility directly and indirectly through the variable age at first marriage. Improving the quality of women's education and increasing income welfare will have an impact on increasing the age at first marriage, and ultimately will reduce fertility.